ANALISIS GAYA KEPEMIMPINAN KHARISMATIK DALAM MEMELIHARA NILAI-NILAI TRADISI KEPESANTRENAN TRADISIONAL DI PONDOK PESANTREN NURUL HUDA KAMUNDUNG SAMPANG - Risalatul Hasanah; Mohammad Kosim (re-JIEM (Research Journal of Islamic Education Management), 2021)
This study examines the charismatic leadership style at the Pondok Pesantren Nurul Huda Kamundung Omben Sampang. This study uses a qualitative approach with the type of field research. Sources of data were obtained using interviews, observation, and documentation. The results show that: first, the application of a charismatic leadership style in maintaining traditional pesantren traditional values ​​still maintains the salaf Islamic boarding school which still maintains the teachings of previous scholars whose teaching uses the yellow book using the sorogan and wetonan teaching methods. And its management does not ask for funds from the government but asks for donations from students, asking for donations from the community to meet the needs of Islamic boarding schools. Second, the way to maintain traditional values ​​in charismatic leadership in Islamic boarding schools is by maintaining the traditions of salaf Islamic boarding schools, meaning that the salaf is still following the teachings of the scholars, namely reciting the yellow book, praying in congregation, learning to read the Qur'an, khidmah, and seek the approval of the teacher, and the method used is deliberation.